Changes in sports injuries incidence over time in world-class road cyclists - Barrios, C.; Bernardo, N. D.; Vera, P.; Laiz, C.; Hadala, M. (International Journal of Sports Medicine, 2015)
This is a descriptive epidemiologic survey on all traumatic and overuse injuries which occurred in 2 groups of male elite road cyclists based on retrospective clinical interviews and physical examinations. The historical group consisted of 65 professional road cyclists surveyed from 1983 to 1995. The contemporary group included 65 elite racers still active and reporting injuries from 2003 to 2009. Injury/cyclist ratio was 1.32 in the historical group and 2.13 in those still active. Traumatic injuries increased from 39.5% (historical) to 53.9% (contemporary) (p<0.05). Severe traumatic lesions decreased from 49.9% in the historical group to 10.5% in the contemporary group (p<0.01). Patellofemoral pain decreased from 28.8% (historical) to 6.1% (contemporary) (p<0.01). Muscle injuries substantially increased from 13.4% to 44.9% (p<0.01). In the historical racers, the rates of risk for traumatic injury were 0.104 per year per cyclist, and 0.003 per 1000 km of training and competition. These figures increased to 0.287 and 0.009 respectively in the contemporary group. In summary, contemporary professional road cyclists are exposed to double the risk of traumatic injuries than those competing in the 80s and early 90s. However, these lesions have less severity. Overuse injuries had a completely different clinical pattern, with the currently active cyclist exhibiting more muscle injuries and less tendinous lesions.